Contribution of Kinesthetic Intelligence and Motor Ability to Futsal Playing Skills - M AGIL ANWAR IBRAHIM; DEFRI MULYANA; AANG ROHYANA (Journal of Physical Education For Secondary Schools, 2022)
Introduction: Kinesthetic intelligence is the ability to move the body obtained by stimulation so that it can create practical and efficient movements in processing an object or creating, changing a form of exercise; experts reinforce this. Purpose: This study aims to find information about the contribution of Kinesthetic Intelligence and Futsal Playing Skills in the Futsal Student Activity Unit. The author is interested in researching this because, in the futsal game, these two things are closely related. Methods: This type of research is descriptive quantitative. The population of this research is the Student Activity Unit for Men's Futsal Players at the University of Siliwangi, totaling 60 Sampling Techniques using Purposive Sampling. Measurement of Kinesthetic Intelligence Using Questionnaires, Measurement of Motor Ability Using Barrow Motor Ability, and Measurement of Futsal Playing Skills Using Games Performance Assessment Indicator. Based on data processing using statistical tests, it turns out that empirically there is a contribution between Kinesthetic Intelligence and Motor Ability together with the results of futsal playing skills of the Student Activity Unit (Unit Kegiatan Mahasiswa/UKM) Male Futsal Players at Universitas siliwangi. Results: The hypothesis results are accepted and included in the High category; the contribution of kinesthetic intelligence skills to playing futsal is 2.89%, the gift of the motor ability to playing skills to futsal is 77.44%, and the contribution of kinesthetic intelligence and motor ability together is 77%. Conclusions: In this case, the contribution of motor ability provides a higher carrying capacity than kinesthetic intelligence. The results of the research that the authors get, therefore the authors suggest that every futsal coach trains together programmed, systematically, and regularly to improve kinesthetic intelligence and motor abilities to be more effective and efficient.